Information contents of the acoustic emission exemplified by the selected physico-chemical processes - MIKIEL, W.; RANACHOWSKI, J.; REJMUND, F.; RZESZOTARSKA, R. (Archives of Acoustics, 1990)
The main sources of the acoustic emission (AE) signals in the physico-chemical processes are the phase transitions, gas evolution and heat of the reaction [1, 2]. Measurements of AE signals in solutions are more difficult than in solids because of low energetic levels. Energies of AE measured for the reactions in solutions are not much higher than the noise level of measuring apparatus; beside this, such interferences as wavy motion, liberation of dissolved gas and liquid mixing noise are present. This is why the investigation of chemical reactions in the solution with AE method necessitates for the application of highly sensitive measuring sets and computer data processing systems.